Investigating the validity and reliability of the functional movement screening tool in tennis - Kazemi, S.; Alizadeh, M. H.; Daneshmandi, H. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Recently, researchers use functional movement tests and especially the functional movement screen (FMS) as a screening tool to prevent injuries in sports. However, limited studies are available to strongly support the validity and reliability of the FMS in different sports populations. Therefore, the FMS does not seem to be a comprehensive FMS tool in order to investigate asymmetry and limitations in all sports. Therefore, the aim of the present study was to design and evaluate the validity and reliability of the screening tool for functional movements in tennis.